A MULTIPHASE THERAPEUTIC COMMUNICATION APPROACH TO ENHANCING INCLUSIVE SUPPORT FOR CHILDREN WITH SPECIAL NEEDS - Surianto Surianto; Zera Edenzwo Subandi; Yesica Yuliani Clara (LPPM Institut Pendidikan Nusantara Global, 2025)
Inclusive education for children with special needs (CSN) in Indonesia remains hindered by limited professional resources, inadequate inclusive infrastructure, and low public acceptance. This community-development based activities aim to address these barriers by implementing a structured therapeutic communication training program to the key stakeholders of Lentera Cita Karya Foundation, an inclusive school in Jakarta. The program targeted teachers, in-house therapists, and parents, through focus group discussions (FGD) designed to explore communication challenges and collaboratively build effective strategies. Over two months, trainings were delivered to 15 CSN, 4 therapists, 4 parents, and 4 teachers. In addition to communication training for adults, children participated in basic public speaking and photography sessions to strengthen their cognitive, affective, and psychomotor skills. The program concluded with a public seminar titled “ACT” (Acceptance, Caring, and Tolerance) attended by approximately 80 people, featuring expert speakers and community engagement sessions to promote inclusive dialogue. The seminar also showcased photos taken by the CSN during the training. Results from the intervention highlight that acceptance emerged as the most significant factor influencing CSN development. The findings underscore the importance of integrative, community-based therapeutic communication in supporting inclusive educational environments.